Geometric features of second mesiobuccal canal in permanent maxillary first molars: a cone-beam computed tomography study - Chi-Chun Su; Yu-Chiao Wu; Ming-Pang Chung; Ren-Yeong Huang; Wan-Chien Cheng; Yi-Wen Cathy Tsai; Chen-Yu Hsieh; Ho-Sheng Chiang; Ching-Yang Chen; Yi-Shing Shieh (Elsevier, 2017)
Background/purpose: Inadequacy to locate the second mesiobuccal canal (MB2) canal leads to the highest probability of endodontic failure in permanent maxillary first molars (PMFMs) and still remains a constant challenge for many clinicians. The aim of this study was to characterize the geometrical features between MB2 and other orifices of examined PMFMs using cone-beam computed tomography images. Materials and methods: A total of 108 teeth qualified in the cone-beam computed tomography image archives were enrolled in the present study. The intersecting point (T) was determined as the perpendicular line (h, altitude of triangle) projected from the vertex of the MB2 canal orifice to mesiobuccal canal orifice-palatal canal orifice line (MB1-P). We measured the geometric features of PMFMs with the MB2 canal, including the interorifice distances, area, altitude, and the ratio between the canal orifices. Results: The average interorifice distance was found to be 1.91±0.59 mm for MB1-MB2, 5.73±0.66 mm for MB1-P, and 4.11±0.79 mm for MB2-P, with significant gender difference for MB1-MB2 distance. For the MB1-T distance, a significant difference was found between genders (P=0.02), with males averaging 1.78±0.07 mm, and females 1.48±0.11 mm. For the MB1-P distance, the majorities of both genders were found in the 20-40% cut-off. A portion of the males exhibited a tendency towards the 40-80% cut-off, while females shifted in the reverse direction towards the 0-20% cut-off. Conclusion: In clinical scenarios, these anatomical characteristics of the root canals system could be beneficial to locating the MB2 canal. Keywords: cone-beam computed tomography, maxillary molar, morphology, root canal